-y+2+10y-9-6>=-3+4y+40-8y

Enter Equation or Inequality


Solve for y in the inequality -y + 2 + 10y - 9 - 6 ≥ - 3 + 4y + 40 - 8y

Step 1: Group the y terms on the left hand side:
(-1 + 10)y = 9y

Step 2: Group the constant terms on the left hand side:
2 - 9 - 6 = -13

Step 3: Group the y terms on the right hand side:
(4 - 8)y = -4y

Step 4: Group the constant terms on the right hand side:
-3 + 40 = 37

Step 5: Form modified inequality
9y - 13 ≥ - 4y + 37

Step 6: Group variables:
We need to group our variables 9y and -4y. To do that, we add 4y to both sides
9y - 13 + 4y ≥ -4y + 37 + 4y

Step 7: Cancel -4y on the right side:
13y - 13 ≥ 37

Step 8: Group constants:
We need to group our constants -13 and 37. To do that, we add 13 to both sides
13y - 13 + 13 ≥ 37 + 13

Step 9: Cancel 13 on the left side:
13y ≥ 50

Step 10: Divide each side of the inequality by 13
13y
13
50
13

y ≥ 3.8

Click this lesson to see the interval notation for y ≥ 3.8